Differential binding partners of the Mis18α/β YIPPEE domains regulates the Mis18 complex recruitment to centromeres - Stellfox, Madison E. (Cell Rep, 2016)
The Mis18 complex specifies the site of new CENP-A nucleosome assembly by recruiting the CENP-A specific assembly factor HJURP (Holliday junction recognition protein). The human Mis18 complex consists of Mis18α, Mis18β and Mis18 binding protein 1 (Mis18BP1/hsKNL2). Although Mis18α and Mis18β are highly homologous proteins, we find that their conserved YIPPEE domains mediate distinct interactions that are essential to link new CENP-A deposition to existing centromeres. We find that Mis18α directly interacts with the N-terminus of Mis18BP1; whereas, Mis18β directly interacts with CENP-C during G1 phase, revealing that these proteins have evolved to serve distinct functions in centromeres of higher eukaryotes. The N-terminus of Mis18BP1, containing both the Mis18α and CENP-C binding domains, is necessary and sufficient for centromeric localization. Therefore, the Mis18 complex contains dual CENP-C recognition motifs that are combinatorially required to generate robust centromeric localization that leads to CENP-A deposition.